The Effect of Internal Communication and Organizational Culture on Employee Performance at PT. Bank SulSelBar Makassar Main Branch - Nurul Maghfirah; Felix Chandra (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This study examines the effect of internal communication and organizational culture on employee performance at PT Bank SulSelBar Makassar Main Branch, where several performance problems were found such as lack of optimal service, work delays, and inefficient use of work time. The research sample is the entire population of employees totaling 81 people selected through saturated sampling technique. Using a quantitative approach with multiple linear regression analysis, the results showed that internal communication and organizational culture simultaneously have a significant effect on employee performance, so it is recommended that companies further encourage employees to set clear work goals in order to improve the effectiveness of performance and achievement of organizational goals.